Synthesis and Biological Activities of Some Mannich Bases of 5-(2-furyl)- 1,2,4-triazole-3-thiones - Cansiz, A.; Servi, S.; Koparir, M.; Altintaş, M.; Digrak, M. (My University, 2001)
A number of Mannich bases of 5-(2-furyl) -1,2,4- triazole-3- thiones (I-X) were prepared. The structures of the compounds have been established by elemental analysis and spectral (IR; 1H-NMR) data. Some selected Mannich bases were screened for their in vitro antibacterial activity against some bacteria, emploging the disk-diffusion technique.